Cobalt-catalyzed C–H cyanations: Insights into the reaction mechanism and the role of London dispersion - Detmar, Eric; Müller, Valentin; Zell, Daniel; Ackermann, Lutz; Breugst, Martin (Beilstein Journal of Organic Chemistry, 2018)
Carboxylate-assisted cobalt(III)-catalyzed C–H cyanations are highly efficient processes for the synthesis of (hetero)aromatic nitriles. We have now analyzed the cyanation of differently substituted 2-phenylpyridines in detail computationally by density functional theory and also experimentally. Based on our investigations, we propose a plausible reaction mechanism for this transformation that is in line with the experimental observations. Additional calculations, including NCIPLOT, dispersion interaction densities, and local energy decomposition analysis, for the model cyanation of 2-phenylpyridine furthermore highlight that London dispersion is an important factor that enables this challenging C–H transformation. Nonbonding interactions between the Cp* ligand and aromatic and C–H-rich fragments of other ligands at the cobalt center significantly contribute to a stabilization of cobalt intermediates and transition states.
Keywords: catalysis; C–H activation; density functional theory; London dispersion; reaction mechanisms

(untitled) - London, F. (Z. Phys., 1930)

(untitled) - London, F. (Trans. Faraday Soc., 1937)

(untitled) - Wagner, J. P.; Schreiner, P. R. (Angew. Chem., Int. Ed., 2015)

(untitled) - Grimme, S.; Schreiner, P. R. (Angew. Chem., Int. Ed., 2011)

(untitled) - Schreiner, P. R.; Chernish, L. V.; Gunchenko, P. A.; Tikhonchuk, E. Y.; Hausmann, H.; Serafin, M.; Schlecht, S.; Dahl, J. E. P.; Carlson, R. M. K.; Fokin, A. A. (Nature, 2011)

(untitled) - Fokin, A. A.; Chernish, L. V.; Gunchenko, P. A.; Tikhonchuk, E. Yu.; Hausmann, H.; Serafin, M.; Dahl, J. E. P.; Carlson, R. M. K.; Schreiner, P. R. (J. Am. Chem. Soc., 2012)

(untitled) - Rösel, S.; Quanz, H.; Logemann, C.; Becker, J.; Mossou, E.; Cañadillas-Delgado, L.; Caldeweyher, E.; Grimme, S.; Schreiner, P. R. (J. Am. Chem. Soc., 2017)

(untitled) - Aikawa, H.; Takahira, Y.; Yamaguchi, M. (Chem. Commun., 2011)

Non-covalent Interactions - Hobza, P.; Müller-Dethlefs, K. (The Royal Society of Chemistry, 2009)

(untitled) - Wheeler, S. E.; Seguin, T. J.; Guan, Y.; Doney, A. C. (Acc. Chem. Res., 2016)

(untitled) - Walden, D. M.; Ogba, O. M.; Johnston, R. C.; Cheong, P. H.-Y. (Acc. Chem. Res., 2016)

(untitled) - Daugulis, O.; Roane, J.; Tran, L. D. (Acc. Chem. Res., 2015)

(untitled) - Wencel-Delord, J.; Glorius, F. (Nat. Chem., 2013)

(untitled) - Yeung, C. S.; Dong, V. M. (Chem. Rev., 2011)

(untitled) - Ackermann, L. (Chem. Rev., 2011)

(untitled) - Chen, X.; Engle, K. M.; Wang, D.-H.; Yu, J.-Q. (Angew. Chem., Int. Ed., 2009)

(untitled) - Bergman, R. G. (Nature, 2007)

(untitled) - Ghorai, D.; Müller, V.; Keil, H.; Stalke, D.; Zanoni, G.; Tkachenko, B. A.; Schreiner, P.; Ackermann, L. (Adv. Synth. Catal., 2017)

(untitled) - Graux, L. V.; Giorgi, M.; Buono, G.; Clavier, H. (Dalton Trans., 2016)

(untitled) - Zell, D.; Warratz, S.; Gelman, D.; Garden, S. J.; Ackermann, L. (Chem. – Eur. J., 2016)

(untitled) - Ackermann, L.; Barfüsser, S.; Kornhaass, C.; Kapdi, A. R. (Org. Lett., 2011)

(untitled) - Ackermann, L.; Althammer, A.; Born, R. (Angew. Chem., Int. Ed., 2006)

(untitled) - Ackermann, L. (Org. Lett., 2005)

(untitled) - Sperger, T.; Sanhueza, I. A.; Schoenebeck, F. (Acc. Chem. Res., 2016)

(untitled) - Ahlquist, M. S. G.; Norrby, P.-O. (Angew. Chem., Int. Ed., 2011)

(untitled) - Hansen, A.; Bannwarth, C.; Grimme, S.; Petrović, P.; Werlé, C.; Djukic, J.-P. (ChemistryOpen, 2014)

(untitled) - Lyngvi, E.; Sanhueza, I. A.; Schoenebeck, F. (Organometallics, 2015)

(untitled) - Ehrlich, S.; Moellmann, J.; Grimme, S. (Acc. Chem. Res., 2013)

(untitled) - Grimme, S. (Wiley Interdiscip. Rev.: Comput. Mol. Sci., 2011)

(untitled) - Li, J.; Ackermann, L. (Angew. Chem., Int. Ed., 2015)

(untitled) - Yu, D.-G.; Gensch, T.; de Azambuja, F.; Vásquez-Céspedes, S.; Glorius, F. (J. Am. Chem. Soc., 2014)

(untitled) - Pawar, A. B.; Chang, S. (Org. Lett., 2015)

(untitled) - Liu, W.; Ackermann, L. (Chem. Commun., 2014)

(untitled) - Cui, J.; Song, J.; Liu, Q.; Liu, H.; Dong, Y. (Chem. – Asian J., 2018)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Grimme, S.; Ehrlich, S.; Goerigk, L. (J. Comput. Chem., 2011)

(untitled) - Krossing, I.; Raabe, I. (Angew. Chem., Int. Ed., 2004)

(untitled) - Leitch, J. A.; Wilson, P. B.; McMullin, C. L.; Mahon, M. F.; Bhonoah, Y.; Williams, I. H.; Frost, C. G. (ACS Catal., 2016)

(untitled) - Kumar, N. Y. P.; Rogge, T.; Yetra, S. R.; Bechtoldt, A.; Clot, E.; Ackermann, L. (Chem. – Eur. J., 2017)

(untitled) - Bu, Q.; Rogge, T.; Kotek, V.; Ackermann, L. (Angew. Chem., Int. Ed., 2018)

(untitled) - Zell, D.; Dhawa, U.; Müller, V.; Bursch, M.; Grimme, S.; Ackermann, L. (ACS Catal., 2017)

(untitled) - Yang, Y.; Buchwald, S. L. (Angew. Chem., Int. Ed., 2014)

(untitled) - Yang, Y.; Liu, P. (ACS Catal., 2015)

(untitled) - Tao, J.; Perdew, J. P.; Staroverov, V. N.; Scuseria, G. E. (Phys. Rev. Lett., 2003)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1997)

(untitled) - Johnson, E. R.; Keinan, S.; Mori-Sánchez, P.; Contreras-García, J.; Cohen, A. J.; Yang, W. (J. Am. Chem. Soc., 2010)

(untitled) - Contreras-García, J.; Johnson, E. R.; Keinan, S.; Chaudret, R.; Piquemal, J.-P.; Beratan, D. N.; Yang, W. (J. Chem. Theory Comput., 2011)

(untitled) - Wuttke, A.; Mata, R. A. (J. Comput. Chem., 2017)

(untitled) - Schneider, W. B.; Bistoni, G.; Sparta, M.; Saitow, M.; Riplinger, C.; Auer, A. A.; Neese, F. (J. Chem. Theory Comput., 2016)

(untitled) - Weigend, F.; Ahlrichs, R. (Phys. Chem. Chem. Phys., 2005)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Zhao, Y.; Truhlar, D. G. (J. Chem. Phys., 2006)

(untitled) - Eichkorn, K.; Weigend, F.; Treutler, O.; Ahlrichs, R. (Theor. Chem. Acc., 1997)

(untitled) - Deglmann, P.; May, K.; Furche, F.; Ahlrichs, R. (Chem. Phys. Lett., 2004)

(untitled) - Ribeiro, R. F.; Marenich, A. V.; Cramer, C. J.; Truhlar, D. G. (J. Phys. Chem. B, 2011)

(untitled) - Klamt, A.; Schüürmann, G. (J. Chem. Soc., Perkin Trans. 2, 1993)

(untitled) - Werner, H.-J.; Knowles, P. J.; Knizia, G.; Manby, F. R.; Schütz, M. (Wiley Interdiscip. Rev.: Comput. Mol. Sci., 2012)

MOLPRO, version 2015.1 (a package of ab initio programs)

(untitled) - Riplinger, C.; Sandhoefer, B.; Hansen, A.; Neese, F. (J. Chem. Phys., 2013)

(untitled) - Riplinger, C.; Neese, F. (J. Chem. Phys., 2013)

(untitled) - Liakos, D. G.; Neese, F. (J. Chem. Theory Comput., 2015)

(untitled) - Neese, F. (Wiley Interdiscip. Rev. Comput. Mol. Sci., 2012)

TURBOMOLE, V7.1, 2015 (TURBOMOLE GmbH, since 2007)
a development of University of Karlsruhe and Forschungszentrum Karlsruhe GmbH, 1989–2007

(untitled) - Furche, F.; Ahlrichs, R.; Hättig, C.; Klopper, W.; Sierka, M.; Weigend, F. (Wiley Interdiscip. Rev.: Comput. Mol. Sci., 2014)

(untitled) - Liu, W.; Richter, S. C.; Mei, R.; Feldt, M.; Ackermann, L. (Chem. – Eur. J., 2016)

(untitled) - Sun, B.; Yoshino, T.; Matsunaga, S.; Kanai, M. (Adv. Synth. Catal., 2014)